2013
DOI: 10.1002/ps.3671
|View full text |Cite
|
Sign up to set email alerts
|

Post‐infection activities of fungicides againstCercospora arachidicolaof peanut (Arachis hypogaea)

Abstract: Pyraclostrobin, penthiopyrad and prothioconazole showed similar systemic mobility within peanut leaves and activities against C. arachidicola, and appear to completely arrest the development of the pathogen at least 2 days post penetration, and limit pathogen colonization even when applications occur after symptom onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Pesticide concentrations in perilla leaves were likely affected by various factors, including the physicochemical properties of the pesticide [28], crop morphology [8], and environmental factors such as weather and cultivation conditions [29]. The pesticide concentrations in perilla leaf were high because they are absorbed systemically and translocated in the plant [18,19]. Paterson et al [30] reported that pesticide translocation and systemic properties significantly influence crop residue levels, while Park et al [31] stated that systemic pesticides are more persistent than non-systemic ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pesticide concentrations in perilla leaves were likely affected by various factors, including the physicochemical properties of the pesticide [28], crop morphology [8], and environmental factors such as weather and cultivation conditions [29]. The pesticide concentrations in perilla leaf were high because they are absorbed systemically and translocated in the plant [18,19]. Paterson et al [30] reported that pesticide translocation and systemic properties significantly influence crop residue levels, while Park et al [31] stated that systemic pesticides are more persistent than non-systemic ones.…”
Section: Discussionmentioning
confidence: 99%
“…Fluxapyroxad and penthiopyrad were tested in this study because they are translocated in plants [18,19]. The test crop—perilla leaf—was cultivated under greenhouse conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Lower incidence was likely due to some combination of (i) loss of symptomatic leaves or leaflets, (ii) development of new leaves, and (iii) curative activity of the fungicides applied. In a recent laboratory study, applications of prothioconazole or pyraclostrobin reduced the numbers of early leaf spot lesions when applied to peanut leaves as late as 7 days after inoculation and restricted the size of lesions by over 60% when applied as late as 13 days after inoculation (Cantonwine et al 2008;Johnson and Cantonwine 2014). In the field, similar leaf spot control was achieved with delayed applications of these systemic fungicides compared to the protectant chlorothalonil (Culbreath et al 2006;Culbreath et al 2010).…”
Section: Figurementioning
confidence: 99%
“…The incubation period for C. arachidicola varies. It is reported to be as little as 6 to 8 days during optimal conditions (Shokes and Culbreath 1997), but 10 to 11 days on susceptible genotypes has been more commonly observed in controlled studies (Cantonwine et al 2008;Johnson and Cantonwine 2014). The incubation period can vary greatly among cultivars.…”
Section: Figurementioning
confidence: 99%
“…In the middle and late stages of growth, infections of multiple pathogens lead to a mixture of symptoms that mainly destroy chlorophyll and reduce photosynthetic rate. Defoliation caused by a large number of spots could severely affect dry matter accumulation and pod maturation, resulting in large yield reductions [15].…”
Section: Introductionmentioning
confidence: 99%